A Study of Green Human Resources Management (GHRM) and Green Creativity for Human Resources Professionals - Ali, Md. Chapol; Islam, K. M. Anwarul; Chung, Soo-Jin; Zayed, Nurul Mohammad; Afrin, Mithila (International Journal of Business and Management Future, 2020)
The concept of green human resource management has recently combined with ecological management in business, urbanization, industrialization and so many so forth. It is mainly responsible for managing human resources work, and these work conditions are good. Green human resource management procedures are fundamentally used to reduce the carbon impression of each worker and the information capital of the holding association. It also plays role in convincing workers to look after resources, and participate in waste management to control pollution. It is recommended that companies should be more aware of each of the capabilities that make human resources management green. The development needs of combining ecological manageability with human resource management. Organizations now recognize that while focusing on money-related benefits, they should think about the social and ecological effects to ensure their manageability. Therefore, this notion has lately taken into account, academic analysts and experts. This paper investigates GHRM practices in organizations based on the many current writings. The study found the importance of GHRM ideas, practices, strategies, and difficulties in the business and other organizations. The study uses documented strategies to observe, collect and dissipate contemporary surveys of green human resource management.